2021
DOI: 10.1088/1755-1315/842/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on current agricultural practices among small-scale rice farmers in Kelantan, Malaysia

Abstract: This study investigates the potential exposure parameters among small-scale rice farmers based on their current agricultural practices under submerged rice systems. Twenty-four rice farmers from the District of Tanah Merah in Kelantan, Malaysia were interviewed about various pesticide exposure parameters (November 2020), followed by the collection of pesticide application information using questionnaire surveys across the whole rice season (December 2020 – March 2021). Overall, the 15 selected rice farmers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Their understanding of the effects of pesticides on human health aligns with earlier studies, supporting the notion that farmers with higher knowledge levels are aware of the negative impacts of pesticides on health [19,20]. Interestingly, most farmers in this study had not undergone specific pesticide handling instruction, a trend observed in prior research where experienced farmers rely on past experiences rather than formal training [7].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Their understanding of the effects of pesticides on human health aligns with earlier studies, supporting the notion that farmers with higher knowledge levels are aware of the negative impacts of pesticides on health [19,20]. Interestingly, most farmers in this study had not undergone specific pesticide handling instruction, a trend observed in prior research where experienced farmers rely on past experiences rather than formal training [7].…”
Section: Discussionsupporting
confidence: 84%
“…Various factors can impact the extent of pesticide exposure in real-field settings. These factors encompass the kind of crop cultivated, the specific pesticide utilized along with its physical and chemical characteristics, the spraying machinery employed, the adoption of personal protective gear, storage practices for pesticide products, proper disposal of empty containers, and the behaviors and expertise of those working with these substances [7]. Toxic chemical from pesticides gradually accumulates in body fat through dermal, oral, and respiratory routes due to improper handling, and it may pose long-term and chronic effects on human health [8].…”
Section: Introductionmentioning
confidence: 99%